Stickable beetle clock - Ariff, Ahmad Fairuz; Raja Ahmad Effendi, Raja Ahmad Azmeer; Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
A clock usually functions as an indicator, keeper and coordinator of time. Various clock designs are produced and named according to where it is placed such as the table clock, the wall clock and the refrigerator magnet clock. However, most of the existing clock designs emphasize only on the expression of time with less consideration toward the emotional and semantic application to product design. Therefore, an attachable beetle clock was designed to portray a fun an interactive approach within the shape and system of a beetle.